2001
DOI: 10.1128/mcb.21.7.2324-2336.2001
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Suppression by Raf-1 and MEK1 Requires MEK- and Phosphatidylinositol 3-Kinase-Dependent Signals

Abstract: Two Ras effector pathways leading to the activation of Raf-1 and phosphatidylinositol 3-kinase (PI3K) have been implicated in the survival signaling by the interleukin 3 (IL-3) receptor. Analysis of apoptosis suppression by Raf-1 demonstrated the requirement for mitochondrial translocation of the kinase in this process. This could be achieved either by overexpression of the antiapoptotic protein Bcl-2 or by targeting Raf-1 to the mitochondria via fusion to the mitochondrial protein Mas p70. Mitochondrially act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
114
2

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(125 citation statements)
references
References 55 publications
9
114
2
Order By: Relevance
“…Collectively, these results demonstrate that inhibition of the ERK1/2 signaling pathway potentiates ZBP-89-induced apoptosis and is consistent with ERK1/2 having an antiapoptotic effect. 9 Although the kinetics of both stress kinases p38 and JNK best correlated with ectopic ZBP-89 expression and induction of apoptosis, p38 activation was not required for ZBP-89-induced apoptosis. Despite p38 kinases being required in some cells for p53-independent activation of apoptosis, 29,30 this pathway was clearly dispensable for ZBP-89-mediated apoptosis.…”
Section: Inhibition Of Erk Activation Potentiates Zbp-89-induced Apopmentioning
confidence: 93%
See 1 more Smart Citation
“…Collectively, these results demonstrate that inhibition of the ERK1/2 signaling pathway potentiates ZBP-89-induced apoptosis and is consistent with ERK1/2 having an antiapoptotic effect. 9 Although the kinetics of both stress kinases p38 and JNK best correlated with ectopic ZBP-89 expression and induction of apoptosis, p38 activation was not required for ZBP-89-induced apoptosis. Despite p38 kinases being required in some cells for p53-independent activation of apoptosis, 29,30 this pathway was clearly dispensable for ZBP-89-mediated apoptosis.…”
Section: Inhibition Of Erk Activation Potentiates Zbp-89-induced Apopmentioning
confidence: 93%
“…6,7 The mitogenic signaling cascade (Ras-MEK1-ERK) suppresses apoptosis through activation of both Raf and Akt/PKB. 8,9 In contrast, the stress-activated kinases, JNK and p38, are signaling pathways that mediate apoptosis initiated by UV irradiation, heat shock, chemotherapy and proinflammatory cytokines. [10][11][12][13] Recently, it has been shown that the phosphorylation and activation of JNK could be regulated either by activation of upstream kinases MKK4/7 or repression of upstream phosphatases.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Infection of cells with retroviral vectors FL5.12 and FL/Doxo cells were infected with retroviral vectors encoding WT or DN p53, constitutively active (CA) (DStuI-MEK-LIDEMANE) or DN MEK1 (MEKLIDA) or an empty retroviral vector (pLXSN), as previously described. [36][37][38] Stably infected (WT and DN p53-and pLXSN-transduced) cells were selected with IL-3 þ 2 mg ml À1 G418 (Geneticin, Invitrogen). 34 Stably infected (DN and CA MEK1, BRAF(WT):ER* and BRAF(V600E): ER*) cells were selected with IL-3 þ 2 mg ml À1 puromycin (Sigma-Aldrich).…”
Section: Limiting Dilution Analysis In Doxorubicinmentioning
confidence: 99%
“…Similarly, activation of the Ras/Raf/MEK/MAPK pathway is associated with protection of cells from apoptosis and inhibition of caspase-3 activation. [28][29][30][31] The MAPK pathway inhibits caspase-9 activity by direct phosphorylation. 32 Allan et al 32 showed that caspase-9 was phosphorylated at Thr 125, a conserved MAPK consensus site targeted by ERK2 in vitro, in a MEK-dependent manner in cells stimulated with epidermal growth factor (EGF) or 12-O-tetradecanoylphorbol-13-acetate.…”
Section: Discussionmentioning
confidence: 99%